Komunikasi Persuasif Terkait Kesadaran Kesehatan Mental dalam Series “Daily Dose of Sunshine”: Analisis Semiotik Ferdinand De Saussure - Hafizah, Nur; Fatimah, Anggun Nadia; Rizki, Menati Fajar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Persuasive communication is a strategy employed to convince and influence others to accept a message without imposing pressure, while still allowing them the freedom to either accept or reject it.In 2023, a medical-themed series titled